A Study on Listening Skills and Perspectives to First Year Students at English Department of Academic Year 2015/2016 - Hadijah, Sitti; Shalawati, Shalawati (J-SHMIC : Journal of English for Academic, 2016)
Good ability in listening means having competence to comprehend information during listening activities. However, Listening skill is still considered as one of the most difficult skills for English language learners although they have been learning English for few years. Hence, this study was designed to gather information about the students’ challenges in listening activities, their perspectives on listening subject, and positive factors on the students’ success in listening. Then, a set of listening test and questionnaire were distributed. Both quantitative and qualitative data were studied to identify the underlying matters in students’ listening skills, addressing challenges, main listening hindrance factors and learning experiences. The findings of this study revealed that the students faced problems in listening because they still could not complete the basic listening skills in the test. Furthermore, Most of them considered that the listening classes are challenging for them due to some problems and difficulties during the teaching and learning activities. Besides that, there were 5 factors influenced the students’ listening skill; lack of practice, limited vocabulary mastery, native speakers’ accent, pronunciation, and uninteresting learning materials. Moreover, their knowledge about English structure and good facilities in listening classes supported them to be able to figure out some challenges in listening activities. In addition, the students realized the important of the listening activities, but assistances from the teachers and some other students were still needed during the teaching and learning activities. In conclusion, having good listening skill still appeared as a challenge for the first year students at English Department of Academic Year 2015/2016.